Load-Bearing Capacity of Incisors Restored Using Fiber-Reinforced Composite Post-Core Systems - Uchikura, Keiichiro; Garoushi, Sufyan; Nagata, Kohji; Vallittu, Pekka K.; Wakabayashi, Noriyuki; Lassila, Lippo (Switzerland, 2025)
Objectives: This study aimed to analyze the load-bearing performance of upper incisors and evaluate the curing of the luting polymer composite at various depths within the canal.
Methods: A total of one hundred maxillary central incisors (10 groups, n = 10/group) were subjected to various restorative techniques. Approach A used Gradia Core for post-core and crown; Approach B employed prefabricated fiber posts (4 mm or 8 mm) with Gradia for luting and core build-up; Approach C used short-fiber composite (everX Flow) for post-core build-up; and Approach D used fiber posts with everX Flow for luting and core build-up. Restorations underwent cyclic fatigue (40,000 cycles at 95 N) and quasi-static fracture testing. Surface hardness of luting polymer composites was also measured.
Results: Data showed that restorations with additional fiber posts (Approaches B and D) had significantly higher load-bearing capacity (p < 0.05), while post material and length had no significant impact (p > 0.05). Short-fiber composite as luting and core material (Approach D) enhanced load-bearing performance compared to Gradia-based restorations (Approach B, p < 0.05).
Conclusions: The use of short-fiber composite as both the post luting and core material in restoring compromised incisors, along with a conventional fiber post, demonstrated favorable results in terms of load-bearing capacity.